A CHECKLIST OF VASCULAR PLANTS OF THE GARMIAN REGION IN KURDISTAN, IRAQ - Hameed, Ahmed Habeeb; Ahmad, Saman A (Science Journal of University of Zakho, 2025)
The current study is based on the fieldwork and study of the vascular plants of the Garmian region (Sulaimani district, Kurdistan, Iraq) from late April 2021 through September 2024, during which period 5,500 plant specimens was collected in 145 different waypoints. A total of 79 families (five each in ferns and gymnosperms, 15 in monocots, and 59 in dicots), 336 genera (two species in Pteridaceae and one species in each of Equisetaceae, Adiantaceae, and Aspleniaceae and one in gymnosperms families, 79 in monocots, and 250 in dicots), and 712 species (six of ferns and gymnosperms, 138 of monocots, and 568 of dicots) were identified. The five greatest families in this study are Asteraceae (47 genera, 107 species), Poaceae (39 genera, 83 species), Fabaceae (24 genera, 81 species), Brassicaceae (19 genera, 36 species), and Lamiaceae (15 genera, 34 species). These families account for 47.89% of the total vascular plant species collected in the region, and the richest genus is Astragalus L., with 15 species